Mechanistically different acting tumor promoters induce consistent qualitative and quantitative changes in protein expression patterns of murine epidermis - Schlatterer-Krauter, Kathrin; Hecker, Erich (Anticancer research, 1999)
Systematic screening of different organs has shown that induction of particular proteins by 12-0-tetradecanoyl-phorbol-13-acetate is specific for mouse skin. Different compartments of skin showed all the same expression. For experimental reasons we focused the analysis performed thereafter on the epidermis. As an end- point of mouse skin tumorigenesis papilloma and carcinoma were also screened for changes in protein expression. We focused our efforts on the characterization and identification of selected, de novo expressed proteins induced by various tumor promoters in murine epidermis. The analysis presented here consists of functional characterization. Having found differences in protein expression in TPA-treated murine epidermis compared with acetone-treated control mice, we then tried to correlate the expression to the signal transduction pathway which the tumor promoter exerts its activity through. For this reason we screened protein expression patterns after topical administration of mechanistically differently acting tumor promoters, which were inflammatives not bearing tumor promoting activity anti-promoters or a combination of tumor promoters with modulators of tumor promotion. The epidermis of untreated newborn mice served as a model for high cellular proliferation and differentiation. Alterations were compared with changes observed after tumor promoter application.